2001
DOI: 10.1111/1469-8986.3850752
|View full text |Cite
|
Sign up to set email alerts
|

Error‐related brain potentials are differentially related to awareness of response errors: Evidence from an antisaccade task

Abstract: The error negativity (Ne/ERN) and error positivity (Pe) are two components of the event-related brain potential (ERP) that are associated with action monitoring and error detection. To investigate the relation between error processing and conscious self-monitoring of behavior, the present experiment examined whether an Ne and Pe are observed after response errors of which participants are unaware. Ne and Pe measures, behavioral accuracy, and trial-to-trial subjective accuracy judgments were obtained from parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
315
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 976 publications
(383 citation statements)
references
References 35 publications
35
315
4
1
Order By: Relevance
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…However, many other studies show no relationship between ERN and error awareness (e.g. Endrass, Franke, & Kathmann, 2005;Endrass, Reuter, & Kathmann, 2007;Gehring & Fencsik, 2001;Nieuwenhuis, Ridderinkhof, Blom, Band, & Kok, 2001;O'Connell et al, 2007). Presence of a large number of studies failing to find a relationship between error awareness and ERN amplitude naturally leads to the conclusion that ERN is not strongly linked to conscious error awareness (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the claim that error detection depends on the internal dynamics of the production system is consistent with Karmiloff-Smith's (1986) finding that 4-12 year-olds detect and correct their speech errors without necessarily having explicit metalinguistic awareness of what the error was. Electrophysiological studies have shown that the conflict signal is generated as part of the production process, and can act independently of conscious awareness (e.g., Nieuwenhuis et al, 2001). Nozari et al's (2011) model makes another testable prediction: monitoring and repair of semantic errors should only depend on the maturity of the semanticlexical part of the production system, as this is where conflict leads to the generation of semantic errors.…”
Section: Discussionmentioning
confidence: 99%
“…2009), and Pe is thought to index conscious evaluation of errors, response strategy adjustments, and/or affective assessment of error (Nieuwenhuis et al. 2001; Overbeek et al. 2005).…”
Section: Introductionmentioning
confidence: 99%